Development microemulsion formulation combination of citronella and red ginger essential oil - Chasanah, Uswatun; Wardhani, Ellen Kusuma; Ermawati, Dian (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2023)
Acne vulgaris is a skin health problem. Citronella oil contains citronellal, geraniol, geranial, β-citronellol, and neral, which have antibacterial properties. Meanwhile, red ginger oil contains gingerol, which has anti-inflammatory properties. These two ingredients are suitable for treating acne vulgaris. The aim of this study are to develop microemulsion formulation combination of citronella and red ginger essential oil. In this experimental study, a microemulsion combination of citronella essential oil and red ginger essential oil was made using Tween 80 as a surfactant and Transcutol® as a co-surfactant, with variations of S-mix (surfactant:cosurfactant) of 3:3, 4:2, and 4.5:1.5 ratios. As an oil carrier, isopropyl myristate is used. The microemulsions are formulated using a titration method. The microemulsion was then tested for characteristics and stability. The results show that the most optimal microemulsion formula was obtained with an S-mix ratio of 4:2 with a globule size of 21.64 nm, a Polydispersion Index of 0.15, and a zeta potential of -3.82. Its pH and viscosity meet the required specifications and are stable.